Effective teaching in gifted education : using a whole school approach - Robinson, Wendy, 1968-; Campbell, R. J. (Robert James) (Abingdon, Oxon, England ; New York : Routledge, 2010)
"Providing a rich evidence base, these and other examples place best practice within a framework of theory and policy. School leaders, Gifted and Talented Co-ordinators and classroom practitioners reading this book will understand the principles behind the practice, as well as how and why to apply the practice in their own schools." "This distinctive book will also be immensely useful to all those involved with Gifted and Talented education programmes and schemes and those following Continuing Professional Development and school leadership programmes, as well as NQTs, M-level students and researchers in education."--BOOK JACKET.
Policy, theory and practice in gifted and talented education. Gift and talented education in England 1952-2009: policy framework and aims -- Personalised learning: theory and practice -- The case studies. Case study 1: differentiated teaching and learning in an urban City Technology College -- Case study 2: gifted education in an inner-city multi-ethnic comprehensive school -- Case study 3: gifted and talented education in a rural comprehensive -- Case study 4: personalisation and gifted and talented provision in a sixth form college -- Case study 5: school ethos, student voice and motivation to learn in a girls' grammar school -- Case study 6: curricular depth, enrichment and interactive teaching in a boys' grammar school -- Case study 7: teaching and learning in an online reading group -- Case study 8: effective teaching and learning in residential summer schools -- Conclusion. Implications for theory and practice.
Includes bibliographical references (p. [161]-164) and index.
Keywords: Gifted children -- Education; Teachers of gifted children